THE IDENTIFICATION OF THE PRODUCTIVE STRATA WITHIN TYNIV-HRUSHIV OIL AND GAS FIELD - Fedoryshyn, D.; Bagriy, I.; Trubenko, A.; Fedoryshyn, S.; Khovanets, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The findings of the geological and geophysical researches reveal the high prospects of Krukenychi Depression in terms of new deposits discovery. Notably, some productive reservoir rocks have been indentified within the Neogene formations of Tyniv-Hrushiv Oil and Gas Field. The major gas capacity is associated with the lower Dashava deposits; that is supported by considerable well rates which were apparent within previously discovered fields. According to the readings of the geophysical well logging, the correlation pattern of prospective strata distribution has been introduced; as a followup, it has been determined what the fluid content is within the lower Dashava age. Consequently, just over the gas-bearing reservoir rocks, the waterbearing strata have been located. The geological structure of the lower Dashava age is featured by the two-meter unit of claystones and siltstones which separate the water-bearing strata from the productive ones. The very feature of the geological structure causes the encroachment of productive horizons; that is proved by the well testing results. The more thorough researches help to define the key factors which influence the distribution of the sand material through the section of the Sarmatian age. Furthermore, it is possible to set up a water and gas ratio within the productive strata.
Keywords: Productive strata; gas condensate field; the lower Dashava age; sandstone; lens; water-bearing horizon